PENERAPAN GAYA MENGAJAR INKLUSI DALAM UPAYA MENINGKATKAN HASIL BELAJAR DRIBBLING PERMAINAN SEPAK BOLA PADA SISWA KELAS XI SMK PARULIAN 1 JI. STADION TELADAN MEDAN TAHUN AJARAN 2017/2018 - Fascal Rio Chandra Sinaga (Universitas Islam Negeri Sumatera Utara Medan, 2018)
The research will be carried out at SMK Parulian 1 Medan. JI address. Medan Exemplary Stadium. This research was carried out in the 2017/2018 academic year in July 2017. The subjects in this classroom action research were class XI SMK Parulian 1 Medan in the 2017/2018 academic year, amounting to 36 students with 20 male students and 16 female students. This research method is Classroom Action Research. Based on student learning outcomes, there was an increase in the process of dribbling learning outcomes in soccer games